Broadband active electrically small superconductor antennas. (16th August 2017) - Kornev, V K; Kolotinskiy, N V; Sharafiev, A V; Soloviev, I I; Mukhanov, O A
Abstract: A new type of broadband active electrically small antenna (ESA) based on superconducting quantum arrays (SQAs) has been proposed and developed. These antennas are capable of providing both sensing and amplification of broadband electromagnetic signals with a very high spurious-free dynamic range (SFDR)—up to 100 dB (and even more)—with high sensitivity. The frequency band can range up to tens of gigahertz, depending on Josephson junction characteristic frequency, set by fabrication. In this paper we review theoretical and experimental studies of SQAs and SQA-based antenna prototypes of both transformer and transformer-less types. The ESA prototypes evaluated were fabricated using a standard Nb process with critical current density 4.5 kA cm −2 . Measured device characteristics, design issues and comparative analysis of various ESA types, as well as requirements for interfaces, are reviewed and discussed.